2015
DOI: 10.1074/jbc.m115.636951
|View full text |Cite
|
Sign up to set email alerts
|

Variable Substrate Preference among Phospholipase D Toxins from Sicariid Spiders

Abstract: Background: Phospholipase D toxins from brown spider venoms can cause disease in humans. Results: Different toxin family members show specificity for lipid substrates with choline or ethanolamine headgroups or can be ambiguous. Conclusion: Spider phospholipase D toxins have evolved diverse substrate preferences. Significance: The diverse substrate preference may be significant for predation and the mammalian toxicity of venom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 77 publications
2
48
0
Order By: Relevance
“…Further studies confirmed these data by showing that recombinant PLD toxins from L. intermedia venom cleave sphingomyelin, lysophosphatidylcholine, and lyso-PAF [28,29], and that a recombinant PLD toxin from L. arizonica venom presented activity on sphingomyelin, lysophosphatidylcholine and lysophosphatidylethanolamine [30]. Since these enzymes from different species of Loxosceles have the ability to hydrolyze a wide range of different phospholipids, they are now classified as Phospholipases-D [5,30]. In an attempt to standardize the nomenclature of these toxins, a classification was proposed based on the amino acid sequence alignment of the various PLDs present in the Loxosceles intermedia venom deduced from cDNA sequences, phylogenetic studies and also on the biochemical and biological properties of these molecules.…”
Section: Nomenclatures and Biochemical Classification Of Brown Spidermentioning
confidence: 63%
See 1 more Smart Citation
“…Further studies confirmed these data by showing that recombinant PLD toxins from L. intermedia venom cleave sphingomyelin, lysophosphatidylcholine, and lyso-PAF [28,29], and that a recombinant PLD toxin from L. arizonica venom presented activity on sphingomyelin, lysophosphatidylcholine and lysophosphatidylethanolamine [30]. Since these enzymes from different species of Loxosceles have the ability to hydrolyze a wide range of different phospholipids, they are now classified as Phospholipases-D [5,30]. In an attempt to standardize the nomenclature of these toxins, a classification was proposed based on the amino acid sequence alignment of the various PLDs present in the Loxosceles intermedia venom deduced from cDNA sequences, phylogenetic studies and also on the biochemical and biological properties of these molecules.…”
Section: Nomenclatures and Biochemical Classification Of Brown Spidermentioning
confidence: 63%
“…The authors argued that because of this broad phospholipase activity exhibited, the term sphingomyelinase-D was very limited, and proposed the term Phospholipase-D [27]. Further studies confirmed these data by showing that recombinant PLD toxins from L. intermedia venom cleave sphingomyelin, lysophosphatidylcholine, and lyso-PAF [28,29], and that a recombinant PLD toxin from L. arizonica venom presented activity on sphingomyelin, lysophosphatidylcholine and lysophosphatidylethanolamine [30]. Since these enzymes from different species of Loxosceles have the ability to hydrolyze a wide range of different phospholipids, they are now classified as Phospholipases-D [5,30].…”
Section: Nomenclatures and Biochemical Classification Of Brown Spidermentioning
confidence: 99%
“…1) crucially also conserved in menorin and FAM151A and B. These different enzymes hydrolyse phosphodiester bonds of a large number of different substrates, ranging from Glycosylphosphatidylinositol (GPI) protein anchors (in GDPD family) to sphingolipid and lysolipid (in Phospholipase D spider toxins [8][9][10][11] .…”
Section: Resultsmentioning
confidence: 99%
“…The analysis showed that while LgRec1 exhibited a small decrease in platelet aggregation when concentration was decreased by half, LgRec2 still maintained its activity at both concentrations (Figure 5A). Next, LgRec2 was assayed for its ability to cleave sphingomyelin, as this is also an intrinsic characteristic of this class of toxins [47]. As shown in Figure 5B, both LgRec2 and LgRec1 exhibited concentration-dependent activity.…”
Section: Resultsmentioning
confidence: 99%